Bihārī vaibhava : Mahākavi Bihārī kī "Bihārī satasaī" para saṃkshipta evaṃ upayogī bhūmikā sahita kevala 100 dohoṃ kā utkr̥shṭa saṅkalana - Singh, Vijay Pal, 1923-; Bihari Lal, 1595-1663.; Rājasthāna Hindī Grantha Akādamī (Jayapura : Rājasthāna Hindī Grantha Akādamī, 1992)
On the works of Kavi Vihārī Lāla, Braj and Hindi poet; includes a selection of 100 couplets from his Satasaī with explanation.
Braj and Hindi.
Includes bibliographical references (p. 159-160).
Mode of access: Internet.
Keywords: Bihari Lal, -- 1595-1663 -- Criticism and interpretation